Higher methylation subtype of malignant melanoma and its correlation with thicker progression and worse prognosis - Yosuke Yamamoto; Keisuke Matsusaka; Masaki Fukuyo; Bahityar Rahmutulla; Hiroyuki Matsue; Atsushi Kaneda (Cancer Medicine, 2020)
Abstract Malignant melanoma (MM) is the most life‐threatening disease among all skin malignancies, and recent genome‐wide studies reported BRAF, RAS, and NF1 as the most frequently mutated driver genes. While epigenetic aberrations are known to contribute to the oncogenic activity seen in various cancers, their role in MM has not been fully investigated. To investigate the role of epigenetic aberrations in MM, we performed genome‐wide DNA methylation analysis of 51 clinical MM samples using Infinium 450k beadarray. Hierarchical clustering analysis stratified MM into two DNA methylation epigenotypes: high‐ and low‐methylation subgroups. Tumor thickness was significantly greater in case of high‐methylation tumors than low‐methylation tumors (8.3 ± 5.3 mm vs 4.5 ± 2.9 mm, P = .003). Moreover, prognosis was significantly worse in high‐methylation cases (P = .03). Twenty‐seven genes were found to undergo significant and frequent hypermethylation in high‐methylation subgroup, where TFPI2 was identified as the most frequently hypermethylated gene. MM cases with lower expression levels of TFPI2 showed significantly worse prognosis (P = .001). Knockdown of TFPI2 in two MM cell lines, CHL‐1 and G361, resulted in significant increases of cell proliferation and invasion. These indicate that MM can be stratified into at least two different epigenetic subgroups, that the MM subgroup with higher DNA methylation shows a more progressive phenotype, and that methylation of TFPI2 may contribute to the tumor progression of MM.